Analgesic Drug Prescription Patterns on Five International Paediatric Wards - Botzenhardt, Sebastian; Rashed, Asia N.; Wong, Ian C. K.; Tomlin, Stephen; Neubert, Antje (Paediatric Drugs, 2016)
AIM: Analgesic and anti-inflammatory drugs are frequently prescribed in paediatrics. Prescribing and dosing patterns in hospitalised children are not well known. This study explores analgesic drug utilisation on five paediatric wards and discusses its findings in comparison with World Health Organization (WHO) guidelines. METHOD: A sub-analysis of a prospective, multicentre, observational cohort study was undertaken. Prescription data of children aged up to ≤18 years were collected between October 2008 and December 2009 on paediatric general medical wards in five hospitals in Australia, Germany, the United Kingdom (UK), Hong Kong (HK) and Malaysia. Analgesic drug prescriptions were analysed for prescribing patterns in terms of dosing, frequency and route of administration. Dosing data were compared with local recommendations and WHO guidelines for children. RESULTS: In the study cohort, 56.8 % (726/1278) of paediatric patients received at least one analgesic drug prescription (1227 prescriptions). The median age of patients with analgesics was 2.2 years [interquartile range (IQR) 0.8-7.3], and the median number of prescriptions per patient was one (IQR 1-2). The most commonly prescribed drugs were oral paracetamol (45.9 %, 563/1227) and oral ibuprofen (19.9 %, 244/1227). Daily doses of paracetamol ranged from 30 mg/kg/day in Germany to 67-68 mg/kg/day in the UK and HK (p < 0.05). For ibuprofen, single doses ranged from 5-6 mg/kg in HK and the UK to 10 mg/kg in Germany and Australia (p < 0.001). Opioid use prevalence was statistically different between the centres and ranged from 0 to 17.6 % (p < 0.001). CONCLUSION: This study provides a comprehensive overview of analgesic drug use of hospitalised children. Similar to primary care data, paracetamol is the most commonly used analgesic. As recommended by WHO guidelines, oral medication was favoured and opioids used in addition to paracetamol and ibuprofen. Overall drug utilisation was in line with local recommendations and WHO guidelines. Differences in use of paracetamol and ibuprofen among countries were seen, indicating that safety concerns are perceived differently. More large-scale safety studies are needed.
EVALuna2:34010